Star wars. The last Jedi [videorecording (Blu-Ray)] - Lucas, George, 1944- (Lucasfilm, 2018)
Having taken her first steps into the Jedi world, Rey joins Luke Skywalker on an adventure with Leia, Finn and Poe that unlocks mysteries of the Force and secrets of the past.